Teaching and Learning of English in Higher Education before, during, and after Pandemic: What differs? - Tifano, Fanny; Petrus, Ismail; Silvhiany, Sary (Universitas Hamzanwadi, 2024)
The COVID-19 pandemic led to the worldwide closure of educational institutions, forcing a shift from face-to-face to fully online learning. As the pandemic subsided, traditional teaching resumed. This study aimed to explore English teaching and learning in higher education across three phases—before, during, and after the pandemic—by examining differences in activities and technology used. A phenomenological approach was employed, with semi-structured interviews for data collection. Purposive sampling selected eight participants—three lecturers and five students—from the English Education Department of Sriwijaya University. The findings revealed that while learning activities were largely similar across the three phases, the technology and media used varied. Before the pandemic, participants had limited exposure to online platforms, but the pandemic introduced them to new digital tools and methods. In the post-pandemic phase, participants embraced more flexibility, adopting face-to-face, online, hybrid, or blended learning models using suitable platforms. This shift has led to a general preference for the post-pandemic approach to English teaching and learning.